Model integracijske politike v odnosu do drugih modelov imigrantskih politik - Bešter, Romana (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2007)
Immigrant policies play an important role in the processes of inclusion of immigrants in the receiving societies. These policies set legal, institutional and other frameworks for the processes of inclusion as well as guidelines for the adaptation of immigrants and the receiving society. The aims of immigrant policies may stretch from assimilation to different forms ofmulticulturalism. Integration policy is a term often used as a general term referring to different immigrant policies. The author argues that integration policy represents only one model of different immigrant policies. The aim of an integration policy is integration of immigrants. Integration is here defined as a multi-way process which demands adaptation from the immigrants as well as from the receiving society. In the process of integration immigrantsbecome active and equal participants in social, economic, legal, political and cultural relations and processes in the receiving state, while maintaining the possibility of expressing and preserving their culture, religion and ethnic affiliation. Distinct characteristics of the model of integration policy in relation to other models of immigrant policies will be presented through the prism of different typologies of immigrant policies.
Keywords: družba; imigranti; society; integracija; integracijska politika; modeli